Medicinal Plants as A Natural Immunity Booster Against Covid 19: A Review - Gautam, Deepak; Regmi, Krishika; Shrestha, Shital; Karki, Pawan (Kalika Journal of Multidisciplinary Studies, 2024)
Medicinal plants have long been valued for their therapeutic properties, especially in boosting immune function. This review explores the role of medicinal plants in enhancing immunity during the COVID-19 pandemic, with an emphasis on plants known for their bioactive compounds and health benefits. A thorough search of online databases resulted in the identification of 115 published articles from 2020 to 2024, which led to the selection of 50 plants commonly used for immune support. Plants include Garlic, Ashwagandha, Neem,Turmeric, Guduchi, Holy Basil, Amla, Aloe Vera, Black Cardamom, Cinnamon, Pomegranate, Guava, Moringa, Black Cumin, Lemon, Lemongrass, Papaya, Green Tea and others. These plants contain bioactive compounds such as flavonoids, alkaloids, and terpenoids, which are believed to possess immune-boosting, anti-inflammatory, and antiviral properties. Garlic, Turmeric, and Ashwagandha are particularly noted for combating oxidative stress and supporting immune function, while Gurjo, Neem, and Amla are valued for their detoxifying and anti-inflammatory effects. These plants, traditionally used during viral infections like the flu and COVID-19, represent a fusion of ancient cultural wisdom and modern scientific research.Future research should focus on clinical validation and pharmacological studies to better understand the efficacy of these plants in immune modulation.